Spectrum of adrenal disorders in a referral hospital of Bangladesh - Hossain, Kazi Nazmul; Ashrafuzzaman, SM; Pathan, Md Faruque; Amin, Md Feroz; Shefin, Sultana Marufa; Afsana, Faria; Rouf, Rushda Sharmin Binte (BIRDEM Medical Journal, 2021)
Background: Adrenal diseases are common and their presentations are variable. This study aimed to determine the frequency and presenting features of various adrenal diseases in a tertiary care hospital of Bangladesh. Methods: This retrospective descriptive study was carried out in Endocrinology in-patient department of BIRDEM General Hospital, Dhaka, Bangladesh, from October 2017 to December 2018. During this time, total 745 patients were screened; out of whom 91 had adrenal diseases. Results: Mean age of the study population was 39.6±11.5 years. Among them, 65.9% were male. Most (75.8%) cases had adrenal insufficiency, followed by endogenous Cushing’s syndrome (8.8%), Conn’s syndrome (6.6%), non-functioning adenoma (3.3%), congenital adrenal hyperplasia (CAH) (2.2%), pheochromocytoma (1%), myelolipoma (1%) and adrenal carcinoma (1%). According to functional status, most (75.8%) were hypofunctional. Of the patients with adrenal insufficiency, secondary adrenal insufficiency was the most common (78.3%). Among the secondary adrenal insufficiencies, 75.9% had iatrogenic adrenal insufficiency and 24.1% had pituitary diseases. Regarding the cases of primary adrenal insufficiency, 20% cases were due to adrenal tuberculosis, 6.6% were due to adrenal histoplasmosis and 73.3% were idiopathic. Most of the adrenal insufficiency patients presented with hypotension (66.7%), followed by gastrointestinal symptoms (76.8%), weight loss (55.1%), hyponatraemia (42%), pigmentation (13%) and hypoglycemia (10%). In this study, 9.9% patients had adrenal incidentaloma. Most of them (88.9%) were benign. Causes of Cushing’s syndrome among the study population were, iatrogenic (66.7%), adrenal (16.7%) and pituitary cause (16.7%). In this study, 16.5% patients had endocrine hypertension and the causes were endogenous Cushing’s syndrome (53.3%), Conn’s syndrome (40%) and pheochromocytoma (6.7%). Of the hypertensive patients, 60% had co-existing hypokalemia. Conclusion: Adrenal insufficiency was the most common adrenal disorder followed by endogenous Cushing’s syndrome, Conn’s syndrome, non-functioning adenoma and other adrenal disorders. Presentations of adrenal disorders are variable. Among the cause of adrenal insufficiency iatrogenic adrenal insufficiency was the most common. Birdem Med J 2021; 11(2): 103-107